Rapid shale gas development accelerated by the progress in key technologies: A case study of the Changning–Weiyuan National Shale Gas Demonstration Zone - Jun Xie (Natural Gas Industry B, 2018)
Shale gas resources in the Lower Silurian Longmaxi, southern Sichuan Basin, are huge, where, the geological setting, unlike that in North America, is quite complicated and ground surface infrastructure is poor. Therefore, adaptable key technologies will be essential to achieve commercial exploitation of shale gas there. In the case study of the Changning–Weiyuan National Shale Gas Demonstration Zone, six series of key techniques were summarized in comprehensive geological evaluation, development optimization, fast and superior drilling of horizontal wells, horizontal-well volumetric fracturing, cluster-well and factory-like operation in well blocks, and highly-efficient and clean exploitation. The above techniques were applied in this field after three rounds of adjustment and optimization, the resulted production rates of shale gas wells were getting higher and higher and the single-well estimated ultimate recovery (EUR) was also rising. Compared with that in the first round, the average EUR of wells in the third round was increased by 128%. In conclusion, the application practices prove that the above series of key techniques with adaptation and flexibility provide a robust technical support for the rapid output of shale gas production in South Sichuan Basin. Keywords: Southern Sichuan Basin, Early Silurian, Shale gas, Exploration and development, Key technologies, Development efficiency, Productivity construction